The Statesman's Yearbook 2004
2112 p.
Keywords: For one hundred and forty years, The Statesman's Yearbook has been relied upon to provide accurate and comprehensive information on the current political, economic and social status of every country in the world. The appointment of the new editor - only the seventh in the book's history - brought enhancements to the 1998-99 edition and these have been continued since then. The 2004 edition is fully updated and contains more information than ever before. A foldout colour section provides a political world map and flags for the one hundred and ninety two countries of the world. In an endlessly changing world, the annual publication of The Statesman's Yearbook gives all the information you need in one easily digestible single volume. It will save hours of research and cross-referencing between different sources, and it is an essential annual purchase.